2019
DOI: 10.1177/1758573218825476
|View full text |Cite
|
Sign up to set email alerts
|

Surgically relevant anatomy of the axillary and radial nerves in relation to the latissimus dorsi tendon in variable shoulder positions: A cadaveric study

Abstract: Background The purpose of this study was to define the relationship of the axillary and radial nerves, particularly how these are affected with changing arm position. Methods Twenty cadaveric shoulders were dissected, identifying the axillary and radial nerves. Distances between the latissimus dorsi tendon and these nerves were recorded in different shoulder positions. Positions included adduction/neutral rotation, abduction/neutral rotation for the axillary nerve, adduction/internal rotation, adduction/neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We found that the axillary nerve was generally located behind the PCHA, so the medial approach did not increase the risk of axillary nerve injury. It is reported that shoulder abduction could protect the axillary nerve and radial nerve when working near the latissimus dorsi tendon insertion [37]. The musculocutaneous nerve is the only nerve that normally appears in the surgical area.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the axillary nerve was generally located behind the PCHA, so the medial approach did not increase the risk of axillary nerve injury. It is reported that shoulder abduction could protect the axillary nerve and radial nerve when working near the latissimus dorsi tendon insertion [37]. The musculocutaneous nerve is the only nerve that normally appears in the surgical area.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other nerves, the musculocutaneous nerve is the only nerve that requires special attention in medial approach. It is reported that shoulder abduction could protect the axillary nerve and radial nerve when working near the latissimus dorsi tendon insertion [ 35 ]. We found that the axillary nerve was generally located behind the PCHA, so the medial approach did not increase the risk of axillary nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the radial nerve passes through the triangular interval just 22.1 ± 3.6 mm distal and inferior to the humeral insertion [13]. This distance is somewhat dynamic such that both nerves are closer to the LDTT insertion in a position of adduction [17]. When the LDTT is performed, the tendon can be safely released directly off the humeral insertion under direct visualization.…”
Section: Functional and Surgical Anatomy Of The Latissimus Dorsi Tendon Transfermentioning
confidence: 99%